An olefin cross-metathesis approach to depudecin and stereoisomeric analogues - Cheng-Sánchez, Iván; García-Ruiz, Cristina; Guerrero Vásquez, Guillermo A.; Sarabia-García, Francisco Ramón (ACS, 2017)
A new total synthesis of the natural product (−)-depudecin, a unique and unexplored histone deacetylase (HDAC) inhibitor, is reported. A key feature of the synthesis is the utilization of an olefin cross-metathesis strategy, which provides for an efficient and improved access to natural depudecin, compared with our previous linear synthesis. Featured by its brevity and convergency, our developed synthetic strategy was applied to the preparation of the 10-epi derivative and the enantiomer of depudecin, which represent interesting stereoisomeric analogues for structure–activity
Keywords: Polímeros; alcohols; hydrocarbons; mixtures; organic polymers; silica